A p-Si/n-GaN diode fabricated by nanomembrane lift-off and transfer-print technique. (23rd September 2019) - Liu, Yang; Wang, Lai; Wang, Lei; Wu, Xingzhao; Hao, Zhibiao; Yu, Jiadong; Luo, Yi; Sun, Changzheng; Han, Yanjun; Xiong, Bing; Wang, Jian; Li, Hongtao
Abstract: In this paper, we successfully demonstrated a high quality p-Si/n-GaN heterojunction diode through van der Waals bonding implemented by nanomembrane lift-off and transfer-print technique. A nanoscale native oxide layer is observed at the interface by transmission electron microscope, which plays a role as passivation-layer. The heterojunction diode has excellent electrical performance with a high rectification ratio of 4.75 × 10 5 at ± 3 V and a low reverse dark current density of 4.03 × 10 –4 A cm −2 at −3 V. In addition, the heterojunction diode responds to both near ultraviolet (375.6 nm) and red light (650 nm) with responsivity of 429.9 mA W −1 and 66.8 mA W −1 (at −3 V) respectively. This result indicates that a large-lattice-mismatched semiconductor heterojunction can be fabricated based on GaN by using transfer-print technique, thereby expanding the operating band of GaN-based detectors from ultraviolet region to visible region.